Signos Neurológicos Blandos y procesos cognitivos en niños escolares mexicanos de 6-11 años (2019)
Neurological Soft Signs (NSS) are indicative of generalized disruptions in neurological networks of cortico-subcortical areas. Their presence leads to problems in children's cognitive development with future academic repercussions. The presence of NSS was assessed and compared in 144 children aged 6 to 11 years of low-medium socioeconomic status from Mexico City and the metropolitan area through the Infant Neuropsychological Maturity Questionnaire (CUMANIN, for its Spanish acronym) and the School Neuropsychological Maturity Questionnaire (CUMANES, for its Spanish acronym). Results indicate significant differences by sex. Girls showed better performance in word articulation. In groups by age, significant differences were found in leximetric-comprehension, visual perception and executive function-errors. Participants showed the presence of developmental NSS which include: language (articulation disorders, oral and written language disturbances, difficulty finding words), psychomotricity, visual perception and other cognitive functions. There are several factors related to those impairments such as age, socioeconomic context and critical stages in child's development. Identification and early diagnosis can reduce the risk of school failure.